(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This study explores the traditional, innovative, and interactive methods of teaching Latin in medical higher education institutions. The research analyzes the effectiveness of each method, their significance in the educational process, and their impact on students’ learning. Additionally, the advantages of teaching Latin based on modern technologies and interactive approaches are highlighted. This work includes scientific and practical recommendations aimed at improving the process of teaching Latin in medical education.